Karakterisasi Variasi Biokomposit [CaCO3 : Bioplastik /Corn Starch] Terhadap Sifat Mekanis dan Mikrostruktur - Setiawan, Agris; Yuliana, Margaretha Tri Budi (Rekayasa Material, Manufaktur dan Energi, 2022)
ABSTRACT The presence limestone can be used as biomaterial for bone support. CaCO3 as matrix biocomposite and bioplastic as reinforce. This work aimed to study the effect of suspension CaCO3 and corn starch as bioplastic in mechanical properties such as tensile strength, flexural strength, shrinkage and also microstructure. The ratio composition of suspension CaCO3 : Corn Starch namely is 20:80 (w/w)%, 30:70 (w/w)%, 40:60 (w/w)%, 50:50 (w/w)% . The dimensions of the tensile test specimen are in accordance with the ASTM D638 type 4 standard, and the dimensions of the flexural test specimen are in accordance with the ASTM D790 standard. Samples are given codes such as specimen A code for composition 20:80 (w/w)%, specimen B code for composition 30:70 (w/w)%, specimen C code for composition 40:60 (w/w)%, and specimen code D for composition 50:50 (w/w)%. Based on the results of the shrinkage measurement, it showed that specimen B had the highest average shrinkage value of 180.011% for the tensile test specimen, and 160.022% for the flexural test specimen. The results of the tensile test and flexural test also showed that specimen B had the highest average value, namely the ultimate tensile strength of 0.110.015 MPa and flexural strength of 0.020.012 MPa. Meanwhile, from the microstructure test, namely SEM-EDX, the results were in the form of a spheroid-shaped specimen morphology and the dominant elements contained in the specimen were C, N, O, and Ca.